Trade-offs between the short and long term effects of residue quality on soil C and N dynamics - Gentile, R; Vanlauwe, Bernard; Chivenge, Pauline P.; Six, Johan (Springer, 2011)
The decline of soil organic matter (SOM) and its associated fertility is one of the most important constraints to enhanced crop productivity in sub-Saharan Africa. Integrated soil fertility management recognizes the potential benefits of the combined use of organic residue and mineral fertilizer inputs for improved crop yield and SOM build up. However, these benefits may be controlled by residue quality. We examined the short- to long-term C and N dynamics following application of different quality residues with and without N fertilizer in a series of experiments comprising different timescales of measurement in a Kenyan Humic Nitisol. The combined results of these studies indicate that residue quality and fertilizer additions alter short-term C and N mineralization. Combining low quality residue and fertilizer inputs immobilized a greater amount of fertilizer-N than high quality residue. Under field conditions, this reduction in available N induced by the combination of low quality residue and fertilizer reduced environmental N losses and created a positive interactive effect on crop N uptake. While input management manipulated short-term nutrient dynamics, it did not influence long-term SOM stabilization. The input of residue, regardless of quality, contributed to long-term soil fertility improvement. In conclusion, organic residue quality can be manipulated to optimize short-term nutrient dynamics while still conferring the same benefits to long-term SOM contents.